Insights Into Mechanism of the Naphthalene-Enhanced Biodegradation of Phenanthrene by Pseudomonas sp. SL-6 Based on Omics Analysis - Cao, Hao; Zhang, Xinyu; Wang, Shuangyan; Liu, Jiading; Han, Dongfei; Zhao, Baisuo; Wang, Haisheng (Frontiers in Microbiology, 2021)
The existence of polycyclic aromatic hydrocarbons (PAHs) in contaminated environment is multifarious. At present, studies of metabolic regulation focus on the degradation process of single PAH. The global metabolic regulatory mechanisms of microorganisms facing coexisting PAHs are poorly understood, which is the major bottleneck for efficient bioremediation of PAHs pollution. Naphthalene (NAP) significantly enhanced the biodegradation of phenanthrene (PHE) by Pseudomonas sp. SL-6. To explore the underlying mechanism, iTRAQ labeled quantitative proteomics was used to characterize the differentially expressed proteins of SL-6 cultured with PHE or NAP+PHE as carbon source. Through joint analysis of proteome and genome, unique proteins were identified and quantified. The up-regulated proteins mainly concentrated in PAH catabolism, Transporters and Electron transfer carriers. In the process, the regulator NahR, activated by salicylate (intermediate of NAP-biodegradation), up-regulates degradation enzymes (NahABCDE and SalABCDEFGH), which enhances the biodegradation of PHE and accumulation of toxic intermediate----1-hydroxy-2-naphthoic acid (1H2Na); 1H2Na stimulates the expression of ABC transporter, which maintains intracellular physiological activity by excreting 1H2Na; the up-regulation of cytochrome C promotes the above process running smoothly. Salicylate works as a trigger that stimulates cell to respond globally. The conjecture was verified at transcriptional and metabolic levels. These new insights contribute to improving the overall understanding of PAHs-biodegradation processes under complex natural conditions, and promoting the application of microbial remediation technology for PAHs pollution.